Multianalytical Study of Laser Pulse Duration Effects in the IR Laser Cleaning of Wall Paintings from the Monumental Cemetery of Pisa. (27th February 2007) - Andreotti, A.; Colombini, M. P.; Nevin, A.; Melessanaki, K.; Pouli, P.; Fotakis, C.
Abstract : The feasibility of laser cleaning for the removal of a variety of surface deposits from fragments of real wall paintings from the monumental cemetery of Pisa using Nd:YAG at 1064 nm at (μ s), (ns), and (ps) regimes is presented. Multianalytical investigations of the samples from irradiated surfaces of fragments were carried out in order to characterize the original and added materials and to detect any laser-induced alterations; analysis included scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), laser-induced breakdown spectroscopy (LIBS), pyrolysis-gas chromatography-mass spectrometry (PY-GC-MS), and gas chromatography-mass spectrometry (GC-MS). The presence of nitrocellulose and pure lead contaminations on the surface of the samples has been identified. Assessment of the laser cleaning has highlighted the importance of the optimization of laser parameters, specifically pulse duration and fluence at the specified wavelength.